In Memoriam — Professor Patrick Commerford (1947–2025) - Ntsekhe, Mpiko (SA Heart Journal, 2025)
It is with deep sadness that we announce the death of Professor Patrick Commerford, who passed on Thursday 25th September, 5 days before his 78th birthday.